Big Horn Medicine Wheel: Ghost Town and Natural Machine of the Gods - Don Stier (Oz, 2002)
The Big Horn Medicine Wheel (BHMW) is a living ghost town. It is also a natural machine used to commune with the spiritual world. It has been serving in such capacity for hundreds, maybe thousands, of years.